2011
DOI: 10.1002/pmic.201100242
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant inhibition of HSP90, its mitochondrial localized homologue TRAP1 and HSP27 by green tea in pancreatic cancer HPAF‐II cells

Abstract: Pancreatic cancer is a deadly disease characterized by poor prognosis and patient survival. Green tea polyphenols have been shown to exhibit multiple antitumor activities in various cancers, but studies on the pancreatic cancer are very limited. To identify the cellular targets of green tea action, we exposed a green tea extract (GTE) to human pancreatic ductal adenocarcinoma HPAF-II cells and performed two-dimensional gel electrophoresis of the cell lysates. We identified 32 proteins with significantly altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
0
31
0
1
Order By: Relevance
“…Green tea and EGCG induce growth inhibition and apoptosis in various pancreatic cancer cell lines (Zhang et al, 2011; Takada et al, 2002). In particular, EGCG inhibits the growth of MIA PaCa-2 pancreatic adenocarcinoma cells with IC 50 in the range of 25-50 μM and induces apoptosis in several studies (Takada et al , 2002; Qanungo et al , 2005; Li et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green tea and EGCG induce growth inhibition and apoptosis in various pancreatic cancer cell lines (Zhang et al, 2011; Takada et al, 2002). In particular, EGCG inhibits the growth of MIA PaCa-2 pancreatic adenocarcinoma cells with IC 50 in the range of 25-50 μM and induces apoptosis in several studies (Takada et al , 2002; Qanungo et al , 2005; Li et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that a green tea extract (GTE) significantly down-regulated LDHA in HPAF-II pancreatic cancer cells using global proteomics profiling (Zhang et al , 2011) Additionally, GTE concomitantly inhibited molecular chaperones heat shock proteins (Hsp) Hsp90, its mitochondrial localized homologue Trap1 (tumor necrosis factor receptor-associated protein 1), Hsp27, phosphor-Akt and induced apoptosis and growth suppression of the cells. These proteomic modifications are likely linked to the alterations in cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inhibiting both TRAP1 and related HSPs may be an effective strategy to manipulate cancers, although this has only been demonstrated at the cellular level (Zhang et al 2011). Zhang's group administered green tea extract (GTE) to human pancreatic ductal adenocarcinoma HPAF-II cells and performed two-dimensional gel electrophoresis of the cell lysates.…”
Section: Apoptosismentioning
confidence: 99%
“…Although TRAP1 and HSP90 seem to work independently and be functionally redundant in mitochondria, use of current inhibitors containing gamitrinibs has not been successful in distinguishing the two. Targeting multiple proteins that are overexpressed in various cancer cells, such as HSPs and TRAP1, may be another strategy for cancer therapy; while not specific, it can be effective, as has been seen with GTEs (Zhang et al 2011). Lee et al tried to develop mitochondrial TRAP1 inhibitors and replaced the isopropyl amine of the Hsp90 inhibitor PU-H71 with the mitochondria-targeting moiety triphenylphosphonium to produce SMTIN-P01, which showed TRAP1-specific activity and had improved cytotoxicity to cancer cells .…”
Section: Inhibitors Targeting Trap1mentioning
confidence: 99%
“…Diverse beneficial effects to prevent cancer, high cholesterol, allergy and diabetes are also reported. [1][2][3][4] Epigallocatechin gallate (EGCG) is a characteristic constituent of green tea and is known to exert diverse effect of green tea.…”
Section: Introductionmentioning
confidence: 99%